Thanatophoric dysplasia: A case report with probable recurrence - Shankari, N Vidhya; Jerry, Antony Leo; Charan, Lakshmi; Raj, Sushmitha (Indian Journal of Child Health, 2017)
Thanatophoric dysplasia (TD) is a congenital, sporadic, and the most lethal skeletal dysplasia caused by new mutation in the fibroblast growth factor receptor 3 gene. At birth, it is characterized by shortening of the limbs (micromelia), small conical thorax, platyspondyly (flat vertebral bodies), and macrocephaly. TD is divided into two clinically defined subtypes: Type I and II which can be differentiated by the skull shape and femur morphology. Ultrasound examination in the second trimester is often straight forward in diagnosing the congenital anomaly. We report a case of preterm stillborn female baby with dysmorphic facies, macrocephaly, micromelia with short stubby fingers and deep skin creases, short limbs, narrow thorax, and protuberant abdomen delivered at our hospital to a 24-year-old multigravida mother with the previous history of first-trimester abortion. The antenatal ultrasound examination showed shortening of long bones with femur-shaped like a telephone receiver. Dysmorphic facial feature, skeletal abnormalities, and histopathological examination lead us to make the diagnosis of TD Type I. We report this case of TD in view of recurrence risk of around 1%, occurring mostly through autosomal dominant mode of inheritance, which may be the possibility in this case.